2018
DOI: 10.1002/admi.201701062
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plume Properties on Thin Film Composition in Pulsed Laser Deposition

Abstract: Despite the apparent simplicity of pulsed laser deposition, consistent deposition of thin films with the desired thickness, composition, crystallinity, and quality still remains challenging. This article explores the influence of process parameters with respect to film thickness and composition, two key aspects for thin films which have a very strong effect on film properties, possible applications, and characterization. Using five perovskite materials, a systematic analysis of different process parameters, e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 81 publications
2
100
0
Order By: Relevance
“…The RBS spectra have flat tops, within the statistical error margins, and RUMP fitting estimated the La/Sr ratio varies by less than 4% throughout the films (see Figure S8, Supporting Information). Target element atomic mass ratios play a key role in determining the composition of thin films deposited by PLD and previous work has demonstrated that lighter elements are often lower in content . This accounts for the deviation in the LSMC stoichiometry which has a lower cobalt content compared to bulk LSMC for films under both compressive and tensile strain.…”
Section: Resultssupporting
confidence: 63%
“…The RBS spectra have flat tops, within the statistical error margins, and RUMP fitting estimated the La/Sr ratio varies by less than 4% throughout the films (see Figure S8, Supporting Information). Target element atomic mass ratios play a key role in determining the composition of thin films deposited by PLD and previous work has demonstrated that lighter elements are often lower in content . This accounts for the deviation in the LSMC stoichiometry which has a lower cobalt content compared to bulk LSMC for films under both compressive and tensile strain.…”
Section: Resultssupporting
confidence: 63%
“…It is worth to stress that whereas it is known that the Sr 3 V 2 O 8 phase is formed under relatively rich oxygen atmosphere, here its presence becomes more prominent at nominally the same oxygen pressure (residual vacuum) but under higher P (Ar). A possible explanation could be that when increasing Ar pressure, scattering of plasma species increases, being more prominent for the lighter elements, and thus a V deficient flux of adatoms should be expected at the film surface, eventually leading to the formation of a substoichiometric ([V/Sr] < 1) oxide, such as Sr 3 V 2 O 8 . The [Sr/V] concentration ratio in the SVO film and its dependence on P (Ar) has been explored by using energy dispersive X‐ray spectroscopy (EDX) and X‐ray photoemission spectroscopy (XPS) (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…This observation implies that the growth process has a large effect on the carrier mobility (and hence the electrical conductivity), probably related to the presence of growth‐induced defects in the film. Indeed, in PLD technique, the use of ultralow pressure (≈10 −7 mbar) during growth has important consequences on the spatial expansion and kinetic energy of the ablated species as well as on the self‐sputtering and backscattering processes . Probably the most obvious is that energetic species can impinge upon the substrate and the growing film, with subsequent creation of various defects including nonstoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, PLD has been demonstrated to be highly effective for growing highly crystallized PbS nanoparticles at room temperature [20,21]. Moreover, the PLD offers the required process latitude to control the composition, microstructure and hence the optoelectronic properties of the produced thin films by almost independently adjusting the various PLD processing parameters, such as laser fluence, repetition rate, substrate temperature, background gas pressure, and the number of laser ablation pulses [22][23][24]. For the PLD of CZTS films, Vanalakar et al have specifically underlined the great progress achieved in the PCE of pulsed-laser-deposited CZTS (PLD-CZTS)-based solar cells over the last few years [25].…”
Section: Introductionmentioning
confidence: 99%